Drag reduction of circular cylinders by porous coating on the leeward side. (19th January 2017) - Klausmann, Katharina; Ruck, Bodo
Abstract : The present paper describes the effect of drag reduction of circular cylinders due to a porous coating on their leeward sides. To investigate the coating effect, experiments were conducted in a wind tunnel of Goettingen type. Systematic drag measurements were carried out for different cylinder configurations and flow velocities. The drag measurements were complemented by pressure and particle image velocimetry (PIV) flow field measurements around selected cylinders. The Reynolds numbers were varied in the subcritical range of 3× 10^4<Re<1.4× 10^5 . The results show that a thin porous layer on the leeward side, either incorporated in the cylinder shape or applied on the cylinder surface, leads to an increase of base pressure on the leeward side of the cylinder. It causes a reduction of drag and dampens oscillation amplitudes when compared to a cylinder without coating. Results obtained for different configurations with varying key parameters (coating angles, layer thicknesses and pore sizes of the porous material) clearly indicate the drag-reducing and amplitude-damping potential of leeward coating. The amount of drag reduction and amplitude damping depends on the combination of key parameters. It was demonstrated that the lowered drag coefficients c_d were almost constant in the tested range of Reynolds numbers. A maximum reduction of drag of 13.2 % was measured. In addition, the results revealed a strong reduction of the pressure fluctuations around cylinders with a leeward coating due to the shift of the vortex region further downstream.